Quantificação do alumínio administrado e excretado em recém-nascidos pré-termo em uma unidade de terapia intensiva neonatal - Oliveira, Sandra Maria Ribeiro de (2008)
Al is a ubiquitous element on the earth crust and is considered a non-essential element for humans since it is not involved in any biochemical process. Aluminum may act as a toxic species when it is introduced directly into the circulatory system. The most exposed patients are those receiving parenteral nutrition, mainly pre-term infants with less than 37 gestational weeks, under total parenteral nutrition. Due to organs immaturity, pre-term infants are vulnerable to the toxic effects of aluminum. The intoxication is related to symptoms such as anemia, bone disease and neurological disturbances. During the period that the patients are under intensive care, they receive nutrients and medication through the parenteral via. Infusion solutions and solutions for parenteral nutrition may be contaminated by aluminum and therefore be a source of this element to babies. This study aimed to evaluate the extent of the contamination of parenteral solutions and medications administered to patients as well as to establish a balance between the aluminum administered together with the parenteral infusion and eliminated by the babies through the urine. For this evaluation, 10 new-born babies, presenting normal renal function and aging from 32 to 36 gestational weeks were selected, independent of sex. All medication, infusion and nutritional solutions, administered to these babies were collected. Daily urine samples of each baby were also collected, as well as the blood at the first and last day in the intensive care unit. The commercial solutions that were used to 12 compound the nutritional solution administered to the patients were also analyzed. The determination of aluminum was carried out by atomic absorption spectrometry. Results showed that all components of solutions for parenteral nutrition were contaminated by aluminum. While infusion solutions (glucose, NaCl 0.9% and Ringer Lactate) presented a mean of 20 μg/L Al, in bags containing nutritional components the Al level was 500 μg/L. Infusion sets (burette and tubing system) increased in 20% the aluminum in the fluid being administered to the patient. The same was observed for the medication, dilution and administration by means of syringes increased the aluminum present in these samples. The balance between the Al administered and excreted by the new-born babies showed that approximately 58% of the Al is not eliminated in the urine. Moreover, 50% of the patients ingested more than 5 μg Al/kg/day, which is the limit recommended by the US Food and Drug Administration (FDA) for patients under total parenteral nutrition. Since the Al in the patient s blood practically did not change between the first and the last day of internment, the noneliminated Al must have been deposited in any part of the patient s body.